The Application of Criminal Sanctions Against Perpetrators of Unauthorized Distribution of Prescription Drugs (A Study of Court Decision Number 83/Pid.Sus/2023/PN Cbi) - Clara Khairunnissa Paulida; Ady Purwoto; Ande Iman Ferrary (JURNAL MAHASISWA YUSTISI, 2025)
The distribution of hard drugs without a permit is a criminal act that endangers public health and violates applicable legal provisions. This study aims to examine the effectiveness of the application of criminal provisions in Law Number 36 of 2009 concerning Health against perpetrators of the distribution of hard drugs without a permit, as well as to assess the independence of judges in making decisions based on Decision Number 83/Pid.Sus/2023/PN Cbi. The method used is normative juridical with a statutory approach, case approach, and conceptual approach. The analysis was carried out comparatively against Law Number 36 of 2009 and Law Number 17 of 2023 concerning Health. The results of the study indicate that the provisions in Article 197 of the 2009 Health Law are still relevant and effective in reaching perpetrators, even though there have been regulatory updates. In addition, judges are considered to have carried out judicial functions independently by considering legal facts and the principle of justice. This study emphasizes the need for consistency in law enforcement to provide proportional legal protection in the health sector.